2012
DOI: 10.1021/ja300546x
|View full text |Cite
|
Sign up to set email alerts
|

On the Accessibility to Conical Intersections in Purines: Hypoxanthine and its Singly Protonated and Deprotonated Forms

Abstract: The dynamics following electronic excitation of hypoxanthine and its nucleoside inosine were studied by femtosecond fluorescence up-conversion. Our objective was to explore variants of the purinic DNA bases in order to determine the molecular parameters that increase or reduce the accessibility to ground state conical intersections. From experiments in water and methanol solution we conclude that both dominant neutral tautomers of hypoxanthine exhibit ultrashort excited state lifetimes (τ< 0.2 ps), which are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 69 publications
8
54
0
Order By: Relevance
“…Regarding the structural elements of these purine derivatives, different authors have correlated the relative deactivation rates observed for the canonical purine nucleobases and their derivatives shown in Scheme 1 with the presence or absence of a substituent at the C2 position of the purine heterocycle, 10 , 11 , 83 , 91 which would hinder the puckering of the C2 carbon, characteristic of the 1 ππ*(L a )/S 0 seam of intersection. Following this reasoning, one would expect 9-methylpurine and the purine free base, both of which lack a substituent at the position C2, to decay back to the ground state on ultrafast time scales, which is not the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the structural elements of these purine derivatives, different authors have correlated the relative deactivation rates observed for the canonical purine nucleobases and their derivatives shown in Scheme 1 with the presence or absence of a substituent at the C2 position of the purine heterocycle, 10 , 11 , 83 , 91 which would hinder the puckering of the C2 carbon, characteristic of the 1 ππ*(L a )/S 0 seam of intersection. Following this reasoning, one would expect 9-methylpurine and the purine free base, both of which lack a substituent at the position C2, to decay back to the ground state on ultrafast time scales, which is not the case.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 39 , 46 However, Barbatti, Thiel, and their co-workers have recently concluded that, although calculations suggest that the C2 puckering is the primary internal conversion pathway in the S 1 (ππ*) state decay to the ground state, substantial participation of the C6 puckering pathway is also expected in adenine and guanine. 38 , 47 49 On the other hand, using hypoxanthine and inosine as model compounds (Scheme 1 ), the groups of Temps and of Peón and Matsika have recently concluded that, although the exocyclic amino group at the C2 position of the guanine chromophore is not essential for the ultrafast internal conversion to the ground state, 10 , 11 C2 puckering is the main deactivation pathway, which is accelerated in hypoxanthine and inosine as a result of the absence of the amino group. Subsequently, Chen and Kohler 12 have proposed that methylxanthine derivatives seem to decay through a pathway that involves the out-of-plane deformation of the five-membered imidazole ring, as originally predicted by Yamazaki et al, 50 because an ethylenic torsion at the C2 position is not possible in these compounds due to the absence of the C2=N3 double bond.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest‐energy absorption maximum of 6‐thioguanine redshifts by 92 nm (10 835 cm −1 ) relative to the absorption maximum of guanine, whereas that of azathioprine, 6‐thiopurine and 2,6‐dithiopurine redshifts by 17 (2309), 57 (6773) and 86 nm (9370 cm −1 ) relative to the purine‐free base . Similarly, the lowest‐energy absorption band of 6‐thio‐2′‐deoxyguanosine and 2′,3′,5′‐tri‐ O ‐acetyl‐6,8‐dithioguanosine redshifts by 90 (10 515 cm −1 ) and 130 nm (13 594 cm −1 ) relative to 2′‐deoxyguanosine , whereas that of S 6 ‐methylthioinosine and 6‐thioinosine redshifts by 42 (5796) and 71 nm (8911 cm −1 ) relative to inosine . A low‐energy absorption tail is also observed in the absorption spectra of 6‐thiopurine, 6‐thioguanine, 6‐thioinosine and 6‐thio‐2′‐deoxyguanosine that extends into the near‐visible region and that is redshifted in going from aqueous to organic solvents .…”
Section: Steady‐state Photophysical Propertiesmentioning
confidence: 99%
“…Additionally, excited state dynamics affected by the deprotonation was also found in hypoxanthine. Neutral hypoxanthine exhibits only an ultrafast decay (<0.2 ps) while deprotonated hypoxanthine shows another much longer decay (19 ps) . It was suggested that the deprotonation on the N9 position may have a long‐range effect in changing the planarity of pyrimidine ring and the C2 puckering, which will finally lead to the differences on the emissive state surface and the accessibility to the conical intersection.…”
Section: Resultsmentioning
confidence: 99%